Formando os formadores: uma an??lise dos Programas de Forma????o continuada dos especialistas em Educa????o do Municipio de S??o Paulo - Almeida, Patricia Helena Ferreira de (2005)
The objective of this work is to make a comparative analysis of the continuous forming programs of specialists (school directors, deputy school directors, pedagogic coordinators and school supervisors) of the Municipal Education Network in S??o Paulo (1989/1996) through the systemizing of documents prepared by the Municipal Education Secretary of the time period being studied now, in an attempt to contribute towards the reflection on the importance of the formation of all the education professionals. It starts with a brief history concerning the emergence of the abilities in the Pedagogy course which create the technicians in education , traversing the theoretical references that deal with professionalism and continuous forming issues. By analyzing the contents, it seeks to interpret notions of professionalism revealed by the documents based on the references of the professional as a technical specialist, reflective professional and critical intellectual, in search of comprehending the intentionality of such forming movements. During the course of the research, the data analyzed showed a convergence between the principles and concepts of the educational policy during the administration of Mayor Luiza Erundina (1989/1992) with the professionalism references of a critical intellectual, while the material selected in the municipal administration of Mayor Paulo Maluf (1993/1996) revealed a trend of fitting with the professionalism references of a technical specialist.